Hubble Space Telescope Photometry of Globular Clusters in M81 - Nantais, Julie B.; Huchra, John P.; Zezas, Andreas; Gazeas, Kosmas; Strader, Jay (The Astronomical Journal, 2011)
We perform aperture photometry and profile fitting on 419 globular cluster (GC) candidates with mV <= 23 mag identified in Hubble Space Telescope/Advanced Camera for Surveys BVI imaging, and estimate the effective radii of the clusters. We identify 85 previously known spectroscopically confirmed clusters, and newly identify 136 objects as good cluster candidates within the 3σ color and size ranges defined by the spectroscopically confirmed clusters, yielding a total of 221 probable GCs. The luminosity function peak for the 221 probable GCs with estimated total dereddening applied is V ~ (20.26 ± 0.13) mag, corresponding to a distance of ~3.7 ± 0.3 Mpc. The blue and red GC candidates, and the metal-rich and metal-poor spectroscopically confirmed clusters, respectively, are similar in half-light radius. Red confirmed clusters are about 6% larger in median half-light radius than blue confirmed clusters, and red and blue good GC candidates are nearly identical in half-light radius. The total population of confirmed and "good" candidates shows an increase in half-light radius as a function of galactocentric distance. Based on observations with the Hubble Space Telescope obtained at the Space Telescope Science Institute, operated by the Association of Universities for Research in Astronomy, Inc., under NASA contract NAS 5-26555. These observations are associated with Program GO-10250 and Program GO-10584.
Keywords: Astrophysics - Cosmology and Nongalactic Astrophysics; galaxies: individual: M81; galaxies: spiral; galaxies: star clusters: general; galaxies: stellar content